An integrated conceptual design study using span morphing technology. (May 2014) - Ajaj, Rafic M; Friswell, Michael I; I Saavedra Flores, Erick; Keane, Andy; Isikveren, Askin T; Allegri, Giuliano; Adhikari, Sondipon
A comprehensive conceptual design study is performed to assess the potential benefits of span morphing technology and to determine its feasibility when incorporated on medium altitude long endurance unmanned air vehicles. A representative medium altitude long endurance unmanned air vehicle based on the BAE Systems Herti unmanned air vehicle was selected. Stability and control benefits are investigated by operating the morphing span asymmetrically to replace conventional ailerons. The Tornado vortex lattice method was incorporated for aerodynamic predictions. The sensitivity of rolling moment generated by span morphing for different flight parameters (instantaneous vehicular weight and angle of attack) is studied. The variation of roll rate (steady and transient response) with span morphing (for constant rolling moment) for different rolling strategies (extension and retraction) is investigated. It turns out that the optimum rolling strategy is to extend one side of the wing by 22% while retract the other by 22%. Operational performance benefits are investigated by operating the morphing span symmetrically to reduce drag, increase endurance and reduce take-off and landing distances. Twenty-two per cent symmetric span morphing reduces the total drag by 13%, enhances the endurance capability by 6.5% and reduces the take-off field length and landing distance by 28% and 10%, respectively.